2020
DOI: 10.1097/aog.0000000000004096
|View full text |Cite
|
Sign up to set email alerts
|

Primary Dysmenorrhea

Abstract: Primary dysmenorrhea is defined as pain during the menstrual cycle in the absence of an identifiable cause. It is one of the most common causes of pelvic pain in women. Dysmenorrhea can negatively affect a woman's quality of life and interfere with daily activities. The pathophysiology of primary dysmenorrhea is likely a result of the cyclooxygenase pathway producing increased prostanoids, particularly prostaglandins (PGs). The increased PGs cause uterine contractions that restrict blood flow and lead to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
130
0
14

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(144 citation statements)
references
References 60 publications
0
130
0
14
Order By: Relevance
“…However, the pathogenesis of PD is complex, and its pathological mechanism remains unclear. Moreover, the current treatment for PD can only alleviate the symptoms in some patients [ 2 ]. Currently, nonsteroidal anti-inflammatory drugs (NSAIDs) seem to be effective in treating PD, but their adverse reactions also pose some health risks [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the pathogenesis of PD is complex, and its pathological mechanism remains unclear. Moreover, the current treatment for PD can only alleviate the symptoms in some patients [ 2 ]. Currently, nonsteroidal anti-inflammatory drugs (NSAIDs) seem to be effective in treating PD, but their adverse reactions also pose some health risks [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, excessive contraction of the uterine muscle layer caused by the increase in menstrual prostaglandin levels has become increasingly stable. [6][7][8] Studies have shown that patients with PD have higher levels of prostaglandins released when their endometrium falls off than healthy women. [3] From the point of view of traditional Chinese medicine (TCM), the cause of PD is mainly dysfunction of the viscera, qi, and blood block and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Dysmenorrhea refers to abdominal pain during menstruation that leads to lumbosacral pain, nausea, loss of appetite, headache, restlessness, insomnia, fatigue, diarrhea, and even syncope [1,2]. Dysmenorrhea can be classified into two main categories: primary dysmenorrhea (PD) and acquired dysmenorrhea (AD) [3]. PD is defined as pain during the menstrual cycle in the absence of an identifiable cause [3].…”
Section: Introductionmentioning
confidence: 99%
“…Dysmenorrhea can be classified into two main categories: primary dysmenorrhea (PD) and acquired dysmenorrhea (AD) [3]. PD is defined as pain during the menstrual cycle in the absence of an identifiable cause [3]. AD refers to dysmenorrhea caused by pelvic organic diseases such as endometriosis, adenomyosis, chronic pelvic inflammation, uterine malformation and so on [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation